Urinary tract infection related to hospitalized patients: A Review - Mateus Ferreira de Siqueira e Silva1; Flávia Cristina Rodrigues de Sena; Ferdinando Agostinho; Karlla Kristinna Almeida Medeiros; Camila Botelho Miguel; Wellington Francisco Rodrigues (Archive of Urological Research - Peertechz Publications, 2017)
Urinary tract infection (UTI) is the most common type of bacterial infection acquired in a hospital and may affect the upper (pyelonephritis) or lower urinary tract (cystitis). UTIs associated with bladder catheterization are extremely common, with infection occurring due to the use of contaminated materials, lack of aseptic insertion techniques, or prolonged catheterization. This study aimed at reassessing hospital protocols and procedures as well as evaluating the causes, etiology, diagnosis, and treatment of UTIs in hospitalized patients. The database was consulted: Medline, Pubmed, Scielo, Latin American and LILACS. The terms used for the search were the following descriptors: infection, urinary tract, symptoms, diagnoses and treatments. As a result, a wide variety of approaches were evidenced, with treatment of the urinary infections (29.63% ), followed by description of general data (25.93%), mechanisms of infection (22.22%), prevention (11.11%) and diagnosis 11.11%). Although Escherichia coli is the most common etiological agent, UTIs can be caused by various other factors such as hospital conditions and the location of the hospital. Linezolid is used to treat gram-positive bacteria, while fl uoroquinolones are used to treat gram-negative bacteria; therefore, urine culture was performed to determine the treatment to be administered. This study highlights an increased resistance to commonly used drugs, which raises an imminent warning for outpatient UTI cases.